Follow Up Report of Examination Result Of Supreme Audit Agency For State Financial Management: Tindak Lanjut Laporan Hasil Pemeriksaan Badan Pemeriksa Keuangan - Citra Nasir (PT Syamilah Literasi Islami, 2024)
The purpose of this research is to determine the implementation of follow-up reports on the results of the Supreme Audit Agency's audit of state financial management. It is hoped that the follow-up to the Audit Result Report from the Supreme Audit Agency will be a way to find out and overcome the occurrence of state losses committed by state financial managers. Even though state finances are not saved from